Analyzing the influence of TikTok on sustainable choices: the moderating role of environmental consciousness - Bufan Zhong; Jie Deng; Xingqi Liu (Acta Psychologica)
The influence of TikTok on consumer purchase intentions and sustainable choices is a burgeoning area of research that holds significant implications for marketing and consumer behavior. This study explores the moderated mediation effect of TikTok influence on sustainable purchase intentions, emphasizing the roles of sustainable attitudes and environmental consciousness. Grounded in social cognitive theory and environmental psychology, data were collected through a cross-sectional approach from active TikTok users. Using SmartPLS (v3.0) for measurement and structural model evaluation, the findings reveal that TikTok influence positively affects sustainable purchase intentions through the mediation of sustainable attitudes. Furthermore, environmental consciousness strengthens this mediating effect, indicating that individuals with higher levels of environmental awareness and concern are more likely to translate their exposure to TikTok content into sustainable purchasing behaviors. This research highlights the critical role of social media platforms in shaping consumer attitudes and behaviors towards sustainability and offers essential theoretical insights and practical implications for marketers and policymakers aiming to promote sustainable consumption through digital channels.